Genetic effects on sleep/wake variation of seizures. (6th March 2016) - Winawer, Melodie R.; Shih, Jerry; Beck, Erin S.; Hunter, Jessica E.; Epstein, Michael P.; ,
Summary: Objective: There is a complex bidirectional relationship between sleep and epilepsy. Sleep/wake timing of seizures has been investigated for several individual seizure types and syndromes, but few large‐scale studies of the timing of seizures exist in people with varied epilepsy types. In addition, the genetic contributions to seizure timing have not been well studied. Methods: Sleep/wake timing of seizures was determined for 1, 395 subjects in 546 families enrolled in the Epilepsy Phenome/Genome Project (EPGP). We examined seizure timing among subjects with different epilepsy types, seizure types, epilepsy syndromes, and localization. We also examined the familial aggregation of sleep/wake occurrence of seizures. Results: Seizures in nonacquired focal epilepsy (NAFE) were more likely to occur during sleep than seizures in generalized epilepsy (GE), for both convulsive (odds ratio [OR] 5.2, 95% confidence interval [CI] 3.59–7.52) and nonconvulsive seizures (OR 4.2, 95% CI 2.48–7.21). Seizures occurring within 1 h of awakening were more likely to occur in patients with GE than with NAFE for both convulsive (OR 2.3, 95% CI 1.54–3.39) and nonconvulsive (OR 1.7, 95% CI 1.04–2.66) seizures. Frontal onset seizures were more likely than temporal onset seizures to occur during sleep. Sleep/wake timing of seizures in first‐degree relatives predicted timing of seizures in the proband. Significance: We found that sleep/wake timing of seizures is associated with both epilepsy syndrome and seizure type. In addition, we provide the first evidence for a genetic contribution to sleep/wake timing of seizures in a large group of individuals with common epilepsy syndromes.